Implementation of Sociodrama Learning Method in Indonesia History Subjects - Aldi Cahya Maulidan; Alex Anis Ahmad; Miftahul Habib Fachrurozi; Dede Wahyu Firdaus (Criksetra: Jurnal Pendidikan Sejarah, 2024)
Abstract: This research is based on the curiosity of the use of sociodrama learning method. The problem of this research is how the use of sociodrama learning method in Indonesian History subject in Senior High School. This research aims to describe the use of sociodrama learning method in Indonesian History subject in Grade 10 Social Studies at Senior High School Number 5 in Tasikmalaya. This research uses qualitative method which is a case study type. The population in this study is the entire activity of social situations consisting of research location in Senior High School Number 5 in Tasikmalaya, informants, and activities of using sociodrama learning methods. Sampling used purposive sampling. Data collection was conducted using observation, interview, and documentation techniques. The analysis was conducted with three stages, namely data reduction, data presentation, and conclusion drawing. The result of the research explained that the background of using sociodrama method was the teacher wanted to increase the motivation and interest of students to learn history. The use of sociodrama method in learning can revive events that happened in the past that can help students in adding imagination, understanding, creative thinking, and students become more interactive when carrying out learning. Abstrak: Penelitian ini didasarkan atas keingin tahukan akan penggunaan metode pembelajaran sosiodrama. Permasalahan penelitian ini yaitu bagaimana penggunaan metode pembelajaran sosiodrama pada mata pelajaran Sejarah Indonesia di Sekolah Menengah Atas. Penelitian ini bertujuan untuk mendeskripsikan penggunaan metode pembelajaran sosiodrama pada mata pelajaran Sejarah Indonesia di kelas X IPS SMA Negeri 5 Tasikmalaya. Penelitian ini menggunakan metode kualitatif yang berjenis studi kasus. Populasi pada penelitian ini adalah seluruh aktivitas situasi sosial terdiri dari tempat penelitian di kelas X IPS SMA Negeri 5 Tasikmalaya, informan, dan aktivitas penggunaan metode pembelajaran sosiodrama. Pengambilan sampel menggunakan purposive sampling. Pengumpulan data dilakukan dengan menggunakan teknik observasi, wawancara, dan dokumentasi. Analisis dilakukan dengan tiga tahapan, yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menjelaskan bahwa latar belakang penggunaan metode sosiodrama adalah guru berkeinginan untuk menambah motivasi dan minat belajar peserta didik terhadap pembelajaran sejarah. Penggunaan metode sosiodrama pada pembelajaran dapat menghidupkan kembali peristiwa yang terjadi di masa lalu yang dapat membantu peserta didik dalam menambah imajinasi, pemahaman, berpikir kreatif, dan peserta didik menjadi lebih interaktif ketika melaksanakan pembelajaran.